Price and Service Quality as Determinants of Customer Loyalty: Evidence from Warung Kopi Alkautsar - Asmaul Husna; Alfi Syahril Fj; Yeyen Servia; Amrusi; Musfiana; Achmad Mustofa (Economic Education Analysis Journal, 2025)
Customer loyalty reflects a customer’s commitment to repurchase products or services. This study analyzes the influence of price and service quality on customer loyalty at Alkautsar Grong-Grong Coffee Shop. Using a quantitative approach, data were collected through questionnaires from 80 respondents determined by the Slovin formula (5% error margin) from a population of 100 customers. Data analysis involved classical assumption tests, multiple linear regression, and hypothesis testing using t-test, F-test, and the coefficient of determination (R²). The results show that price significantly affects customer loyalty with t-value 4.802 > t-table 1.99125 and sig. 0.000 < 0.05. Service quality also significantly affects loyalty with t-value 5.510 > t-table 1.99125 and sig. 0.000 < 0.05. Simultaneously, price and service quality influence loyalty with F-value 20.862 > F-table 3.12 and sig. 0.000 < 0.05. The R² value of 0.334 (33.4%) indicates that customer loyalty is explained by price and service quality, while 66.6% is influenced by other factors. Thus, competitive pricing and superior service quality enhance customer loyalty.